Democracies, leaderships, equalities. Two suggestions by Herodotus and Thucydides (Revista Archai, 2022)
This text investigates the problem of majority decision in democracies from three paradigmatic passages from Herodotus and Thucydides, and examines their implications for the forging of leadership, for the promotion of crises and, chiefly, for the identification of different modes of equality. From the examination of Herodotus 6.109.5 and 8.79.3, and Thucydides 3.35-50, parallels are drawn which, starting from ancient problems, may shed some light on contemporary analogue problems.